Plasma vitamin a and β-carotene levels in pregnant and non-pregnant holstein cows - Seyfullah Haliloğlu; Ahmet Semacan; Nuri Başpınar; Gökhan Doğruer (Eurasian Journal of Veterinary Sciences)
This study was carried out to determine the changes of β-carotene and vitamin A levels on pregnant and nonpregnant cows, on 20 primiparous Holstein cows with same management conditions. The vaginal, rectal and ultrasonographic examinations were conducted on cows to determine the reproductive problems. The cows without reproductive problem were synchronised and inseminated. A total of 11 blood samples were taken per cow between 0 to 23 days post-insemination, the plasma p-carotene and vitamin A levels were determined spectrophotometry ally. The examination of the pregnancy was carried out ultrasonographically on 25th day post-insemination and the cows were divided into two groups as pregnant (n= 11) and non-pregnant (n=9). In our study, although we observed a positive correlation between β-carotene and vitamin A levels in pregnant cows, no relation was seen in non-pregnant cows. Moreover, regarding β-carotene levels, an important difference was recorded between pregnant and non-pregnant cows, but no difference in respect with vitamin A between both groups. As a result, we have concluded that the rich feeding in regard to β-carotene is useful for the increase of the fertility rate in cows exposed to close shed rearing.